2010
DOI: 10.1111/j.1872-034x.2010.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for clinical utility of GPC3, measured by a commercially available ELISA kit with Glypican‐3 (GPC3) antibody, as a serological and histological marker for hepatocellular carcinoma

Abstract: We did not find serum GPC3 level, measured by a commercially available ELISA kit with GPC3 antibody, to be useful in the diagnosis of HCC. However, we did observe increased GPC3 staining in HCC tissue with moderate or poor differentiation, suggesting that GPC3 is produced by HCC tumors. This lack of utility could have been due to the measuring procedure used in the present study. Further evaluation of GPC3 in HCC with other measuring procedures is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 34 publications
2
52
0
Order By: Relevance
“…Our results were in agreement with Young et al (2003), Li et al (2006), Youssef et al (2010), Yan et al (2011), Gomaa et al, (2012 who found that the percentages of mRNA expression in HCC patients were (100%, 90%, 76%, 80.5%, and 85%) respectively. Several other studies reported similar results, Jackbovic et al (2007); Nishimura et al (2008);Yasuda et al (2010) concluded that GPC-3 mRNA is significantly up regulated in HCC compared to normal and benign liver samples, and hence GPC-3 could serve as a molecular marker for early detection of HCC.…”
Section: Discussionsupporting
confidence: 52%
“…Our results were in agreement with Young et al (2003), Li et al (2006), Youssef et al (2010), Yan et al (2011), Gomaa et al, (2012 who found that the percentages of mRNA expression in HCC patients were (100%, 90%, 76%, 80.5%, and 85%) respectively. Several other studies reported similar results, Jackbovic et al (2007); Nishimura et al (2008);Yasuda et al (2010) concluded that GPC-3 mRNA is significantly up regulated in HCC compared to normal and benign liver samples, and hence GPC-3 could serve as a molecular marker for early detection of HCC.…”
Section: Discussionsupporting
confidence: 52%
“…Eight of these studies (22,24,26,27,30,31,33,35) compared the diagnostic accuracy of GPC3 with AFP for HCC in the same patients. Finally, four studies clearly indicated serum GPC3 performed better than AFP for the diagnosis of HCC (22,25,33,34), two studies had the opposite conclusion (12,24), and the remaining studies did not clearly show a difference. Pooled sensitivity and specificity of GPC-3 for HCC were 55.2 and 84.2%, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…The expression of OCI-5, a rat homologue of GPC3 was found to gradually increase during the occurrence and progression of HCC in a rat model. Furthermore, data obtained from different studies (18)(19)(20) and in our laboratory (unpublished data) have revealed that GPC3 expression is correlated with such clinical features of HCC as tumor staging, differential degree and invasive ability. HCC patients with increased levels of GPC3 have relatively shorter survival rates than those with lower GPC3 expression, indicating that elevated levels of GPC3 could be an independent factor of poor prognosis in HCC (21).…”
Section: Discussionmentioning
confidence: 99%